Postcolonial criticism encounters late Ottoman studies - Kechriotis, Vangelis (Historein, 2013)
In Ottoman studies, it is only in the last decade that colonialism has been considered a useful analytical category. This may be partly due to the fact that, in the 1970s and 80s, especially in approaches which drew on the dependency theory and the integration of the Ottoman Empire into the world economy, the latter was studied as one of those regions which was never effectively colonised. However, recently postcolonial studies have attracted the interest of nineteenth-century historians who have reversed the argument and tend to include the Ottoman Empire not among the states that were subject to colonisation but among the colonisers. However, the focus remains on power relations among Muslims. This article offers a critical overview of this literature. It also suggests possible ways for a similar analytical category to be used for Muslim-Christian relations as well.